2022
DOI: 10.1177/17562848221074208
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotherapy for irritable bowel syndrome: patient expectations and perceptions

Abstract: Introduction: Numerous studies have shown that hypnotherapy (HT) is effective in irritable bowel syndrome (IBS) using traditional symptom severity end points. However, there is now interest in capturing the patient’s perception of their illness and treatment because what patients expect from their treatment may differ from that of their healthcare provider. Objective: To record patient perceptions and expectations of hypnotherapy as well as their symptom response. Methods: 150 consecutive IBS patients (116 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…21 Interestingly, symptom responses did not differ according to patient preferences for mode of delivery. While it would be worth confirming these findings in future studies with larger sample sizes, this is consistent with the literature on patient perceptions 22 and satisfaction 23 with face-to-face GDH, which have suggested that focusing on symptom responses only does not fully capture the patients experience of treatment. Based on our findings and the existing literature, it is not possible to know whether those who felt they would have had additional benefit from face to face would have had a greater symptomatic benefit.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…21 Interestingly, symptom responses did not differ according to patient preferences for mode of delivery. While it would be worth confirming these findings in future studies with larger sample sizes, this is consistent with the literature on patient perceptions 22 and satisfaction 23 with face-to-face GDH, which have suggested that focusing on symptom responses only does not fully capture the patients experience of treatment. Based on our findings and the existing literature, it is not possible to know whether those who felt they would have had additional benefit from face to face would have had a greater symptomatic benefit.…”
Section: Discussionsupporting
confidence: 87%
“…Based on our findings and the existing literature, it is not possible to know whether those who felt they would have had additional benefit from face to face would have had a greater symptomatic benefit. Indeed, the aforementioned studies on face-to-face GDH have shown that patient expectations of a positive outcome 22 and patient satisfaction 23 do not necessarily influence symptom responses.…”
Section: Discussionmentioning
confidence: 99%
“…Gut-focused hypnotherapy (GFH) can not only improve the primary symptoms of IBS but also reduce noncolon symptoms, anxiety, and depression and improve quality of life and cognitive function [ 194 , 195 ]. Hypnotherapy is particularly effective in children with IBS [ 189 , 196 , 197 ].…”
Section: Hypotherapy and Ibsmentioning
confidence: 99%
“…However, the main limitation of this randomized study was the lack of long-term follow-up data to determine the persistence of the effects of abbreviated hypnotherapy, which should be examined in the future. The relevant studies supporting the utility of hypnotherapy in IBS treatment are shown in Table 1 [ 85 , [182] , [183] , [184] , [185] , [186] , [187] , [188] , [189] , 191 , [193] , [194] , [195] , [196] , [197] , 199 , 202 ].…”
Section: Hypotherapy and Ibsmentioning
confidence: 99%
See 1 more Smart Citation